A naturalistic virtual reality task reveals difficulties in time-based prospective memory and strategic time-monitoring in children with ADHD - Erik Seesjärvi; Sascha Zuber; Emilie Joly-Burra; Matthias Kliegel; Juha Salmi (Scientific Reports)
Abstract Time-based prospective memory (TBPM), which supports executing everyday actions at appropriate times, is a key cognitive skill generally weaker in individuals with attention-deficit/hyperactivity disorder (ADHD). To better understand the mechanisms of TBPM, we used a naturalistic virtual reality task called Executive Performance in Everyday LIving (EPELI) to study TBPM in 71 children with ADHD and 71 typically developing peers aged 9–13 years in an ecologically relevant context. Our results revealed that children with ADHD showed lower performance on TBPM tasks not because of how frequently they monitored the time overall, but because they did so less strategically. More specifically, the degree of strategic time monitoring accounted for 22.1% of variance in TBPM performance and fully mediated the effect of ADHD. Together, the absolute frequency of clock-checking, the degree of strategic time monitoring, and ADHD status explained 53.9% of the variance in TBPM performance. As monitoring strategies can be trained, the present findings may have important implications for targeted support to help individuals with ADHD manage their schedules.